COMPUTER ASSISTED DESIGN (CAD) EDUCATION AT THE INDUSTRIAL ENGINEERING FACULTY, UNMSM - Rojas Lazo, Oswaldo (2006)
CAD teaching at the Faculty of Industrial Engineering of the UNMSM, is the subject of this work Having as a reference the curriculum, the courses are analyzed that can develop these contents with or without software application, the four basic components of a CAD system are analyzed: software, hardware, humanware and data base.